Abnormal WBC Scattergrams by Sysmex XN550, A Supplementary Diagnostic Tool for Malaria to the Conventional Methods - Bute, Rajeshwar Suresh; Bharambe, Bhavana Madhukar; Pawar, Ravikiran; Jadhav, Asawari Bharat (Annals of Pathology and Laboratory Medicine, 2021)
Background: In India, malaria has a major impact on health system. It is usually diagnosed based on symptomatology, parasite detection in the peripheral smear (PS) or rapid diagnostic tests (RDT) such as malaria antigen test (MAT). Detection of malaria by MAT is considered as the gold standard. A rapid, cost effective screening of malaria can be done with the automated analyzers. The present study was undertaken to assess the efficacy of WBC scattergram generated by Sysmex XN 550 hematology analyzer to diagnose malaria. Methods: A prospective study was conducted over a period of 4 months from August to November 2019, after obtaining institutional ethical clearance. All cases diagnosed as Plasmodium vivax / Plasmodium falciparum infections on malaria antigen test (MAT) were included. Their hemogram and WBC scattergrams obtained from Sysmex XN 550 were studied. Thick & thin Smears were made and stained with Leishman’s stain for microscopy. Results: A total of 101 cases were diagnosed as malaria positive by MAT and thick smear. Ninety-seven were positive by Leishman’s stain. Abnormal scattergrams were 81 out of 101 malaria positive cases. The commonest pattern was double neutrophil zone (n=22) followed by double neutrophil with less space between neutrophil and eosinophil (n=17). An abnormal event on X axis was observed in 16 patients. Gray zone and double eosinophil areas were observed in 11 and 4 cases respectively. The sensitivity of the analyzer was found to be 80.19%. Conclusion: Scattergram of automated haematology analyser (Sysmex XN 550) has good sensitivity, which can be increased to a better level if combined with thrombocytopenia and symptomatology of the patients.